ОСОБЕННОСТИ ОБУЧЕНИЯ ИНОСТРАННОМУ ЯЗЫКУ ДЕТЕЙ ДОШКОЛЬНОГО ВОЗРАСТА - Есбергенова, Г.; Ганиева, З. (SCIENCE and SOCIETY, 2018)
The article deals with the issues of teaching foreign language at pre-school and elementary stages of learning. The use of different games at the lesson promotes to the creation of the friendly atmosphere, growth of collective knowledge in the classroom.
Keywords: game; cartoon; primary; kids; learn; tale; song; language; foto; motivation